Evaluation Of Generic Medicines Substitution Practices Among Community Pharmacists In Malaysia And Australia - Chong, Chee Ping (2010)
Many countries including Australia have developed a generic substitution policy designed to reduce medicines expenditure. In Malaysia, the government is facing a similar challenge of managing increasing medicines expenditure. However, unlike Australia, the Malaysian government has not yet implemented the generic substitution strategy. This thesis will provide some baseline data and guideline for the development of a generic substitution policy in Malaysia through direct comparison of issues around generic substitution among community pharmacists in both countries. The study aims to evaluate and compare the perceptions, knowledge and practices of generic substitution among the Malaysian and Australian community pharmacists. The patients’ acceptance toward substitution and the resulting costsaving were also evaluated and compared between the two countries. This was a nationwide cross-sectional descriptive study. Part I of the study involved a questionnaire to assess the pharmacists’ perceptions and knowledge of generic substitution. In the Part II study, data were progressively collected across the multi-sources brand name medicines requests encountered by the pharmacists. The entire populations of 1419 Malaysian community pharmacies were invited in both Part I and II studies via mail. In Australian scene, the recruitment of participants in Part I study was via self-selection using an anonymous web based survey. A national representative sample of 500 Australian community pharmacies were randomly selected and invited via mail in the Part II study.